2021
DOI: 10.1007/s40123-021-00424-4
|View full text |Cite
|
Sign up to set email alerts
|

Standalone Implantation of 2–3 Trabecular Micro-Bypass Stents (iStent inject ± iStent) as an Alternative to Trabeculectomy for Moderate-to-Severe Glaucoma

Abstract: Introduction: This retrospective consecutive study compared standalone implantation of multiple (2-3) trabecular micro-bypass stents (iStent inject ± iStent) (Multi-Stent group) vs trabeculectomy ? mitomycin C (Trab group) in moderate to severe open-angle glaucoma (OAG). Methods: Eligible patients underwent Multi-Stent or Trab surgery from 2018 to 2020 and had at least 3-month follow-up; visual field mean deviation (VF MD) -6 dB or worse; inadequate prior response to maximum medications ± laser procedures; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…This favorable risk-benefit profile of trabecular bypass procedure was corroborated in a recent comparative study of 2–3 trabecular bypass stents versus trabeculectomy, which showed substantial reductions in IOP and medications for both procedures, but significantly higher percentage of safety-adjusted treatment success in the trabecular micro-bypass versus trabeculectomy group. 16 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This favorable risk-benefit profile of trabecular bypass procedure was corroborated in a recent comparative study of 2–3 trabecular bypass stents versus trabeculectomy, which showed substantial reductions in IOP and medications for both procedures, but significantly higher percentage of safety-adjusted treatment success in the trabecular micro-bypass versus trabeculectomy group. 16 …”
Section: Discussionmentioning
confidence: 99%
“…35 , 36 Furthermore, the incremental benefits of additional stents (eg, 3 vs. 2 vs. 1 stent), such as additional IOP reduction and reduced medication burden, have been validated in both preclinical and clinical studies, with favorable safety in all treatment groups. 16 , 33 39 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations